Learning to care of the new born: care consistent with the culture (2010)
This article is the result of the final graduation work necessary to be eligible for the title of Specialized Nurse in Perinatal Maternal Nursing, which was aimed at formulating a proposal for the nursing care to the newborn from a cultural pointofview, basedonthe care practicesthatteenagemothers give their children during the puerperium. The aforementioned proposal was developed based on the results obtained from the research "Care practices given by teenage mothers to their newborns during the puerperium" carried out by Nancy Lucía Bejarano et al., in 2002 (1), in two high birth rates cities of Colombia. The proposal for care was designed as of an exploratory, descriptive and documentary study with a qualitative approach, since the base investigation, data collection and bibliography revision were taken into account. This proposal considers the care practices related to two spheres found in the base research: 1) to favor the closure of transitory openings with which the newborn comes, and 2) to avoid the entrance of cold and heat in order to search for the balance in its body. It also suggests an alternative for health care, applying the nursing knowledge from the cultural perspective, using as point of departure Madeleine Leininger's theory.